2014
DOI: 10.1038/tp.2014.122
|View full text |Cite
|
Sign up to set email alerts
|

A combination of physical activity and computerized brain training improves verbal memory and increases cerebral glucose metabolism in the elderly

Abstract: Physical exercise interventions and cognitive training programs have individually been reported to improve cognition in the healthy elderly population; however, the clinical significance of using a combined approach is currently lacking. This study evaluated whether physical activity (PA), computerized cognitive training and/or a combination of both could improve cognition. In this nonrandomized study, 224 healthy community-dwelling older adults (60–85 years) were assigned to 16 weeks home-based PA (n=64), com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 64 publications
2
95
0
Order By: Relevance
“…Two studies did not provide data to conduct the metaanalysis. Three studies were not included because only eventrelated potential data were presented (Anderson et al 2013;Berry et al 2010), and one study only provided metabolic data (Shah et al 2014). Thus, 21 studies were included in analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not provide data to conduct the metaanalysis. Three studies were not included because only eventrelated potential data were presented (Anderson et al 2013;Berry et al 2010), and one study only provided metabolic data (Shah et al 2014). Thus, 21 studies were included in analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In humans, a 16 week intervention including unsupervised physical activity, computer based brain training, or both found that older adults (60-85 years) who completed both training types had significantly higher long-term verbal memory compared to the control group (Shah et al 2014). Intervention studies that have included physical activity, cognition and emotional or cultural training have suggested that the combination of physical and cognitive training can improve both cognitive performance and functional outcomes in healthy older adults (Oswald et al 2006;Pieramico et al 2012), although this difference disappears when physical and cognitive activity interventions are compared to an active control group (Lautenschlager & Cox, 2013;D.…”
Section: Combined Cognitive and Physical Activity Interventionsmentioning
confidence: 99%
“…Exercise also increases neuronal dendrite spine formation and synaptic proteins (Lin et al 2012). In humans, observational and interventional studies found associations of exercise with beneficial cognitive effects in Alzheimer patients or elderly subjects (Rolland et al 2000;Laurin et al 2001;Shah et al 2014;Vidoni et al 2015).…”
Section: Hsf1 Inducers and Cognitive Preservationmentioning
confidence: 99%